LGBTQs and LAW’S Violence Within a Heteronormative Landscape - Donnelly-Drummond, Anthony (Frontiers in Sociology, 2021)
This article raises concerns as to the way in which some laws may be viewed as both violent, and, as a catalyst for violence against LGBTQ people. In the first instance the concept of heteronormativity and its ramifications are aired. The possible impact of exemptions related to religious organisations and discrimination on grounds of sexual orientation under Northern Ireland’s Equality Act 2006, underscored by the Asher’s cake incident, is then reviewed. The effect of exemptions under the Equality Act 2010 feasibly lending support for protestors against inclusion of LGBTQ issues in a Birmingham school is then set out. Other aspects of law such as those concerning who is included under definitions of adultery on grounds for divorce in any marriage, and, the subject of Voir Dire bias amongst jurors are briefly reviewed. Thereafter the issue of LGBTQ inclusion in curricula is raised and the impact and legacy of section 28 is aired before discussion turns to the situation faced by all students within a heteronormative education system. Overall, the article raises the spectre that apparent top-down discrimination remains largely unchallenged. Moreover that some law may be perceived as inherently violent impacting negatively on LGBTQ people, and, that its violence acts to inflame homophobia whilst enabling homophobes to appear both right and likeable.